2018
DOI: 10.1038/s41420-018-0087-9
|View full text |Cite|
|
Sign up to set email alerts
|

Notch3/VEGF-A axis is involved in TAT-mediated proliferation of pulmonary artery smooth muscle cells: Implications for HIV-associated PAH

Abstract: The incidence of pulmonary arterial hypertension (PAH) is a significant co-morbidity observed in HIV (+) individuals. Pulmonary artery smooth muscle cells (PASMCs)—key components of the arterial vessel wall that regulate vessel diameter, demonstrate increased proliferation and hypertrophy in the lungs of HIV infected individuals, underscoring the role of these cells in the pathogenesis of HIV-associated PAH. While several pathways have been implicated in enhanced proliferation of PASMCs, detailed molecular mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Notch signaling participates in multiple physiological vascular processes, such as proliferation and apoptosis ( 56 ). Notch-1 is associated with PA-EC proliferation ( 57 ), while Notch-3 is highly expressed in PA-SMCs and promotes PA-SMC proliferation via vascular endothelial growth factor ( 58 ). As miR-30d-5p was associated with PA-SMC proliferation and apoptosis, we hypothesized an association between miR-30d-5p and Notch-3.…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling participates in multiple physiological vascular processes, such as proliferation and apoptosis ( 56 ). Notch-1 is associated with PA-EC proliferation ( 57 ), while Notch-3 is highly expressed in PA-SMCs and promotes PA-SMC proliferation via vascular endothelial growth factor ( 58 ). As miR-30d-5p was associated with PA-SMC proliferation and apoptosis, we hypothesized an association between miR-30d-5p and Notch-3.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular HIV-Tat can bind integrins and vascular endothelial growth factor receptors via the c-terminal domain, containing an Arg-Gly-Asp (RGD) sequence and/or a basic domain 127 , 128 . Tat, on binding to these receptors, triggers signaling pathways that affect diverse processes, culminating in the pathogenesis of several HIV-associated co-morbidities – ranging from pulmonary hypertension to cognitive abnormalities 129 , 130 . Previous studies suggest that Tat acts as a proto-cytokine, which modulates the key functions of various cell types, including endothelial cells (ECs) as well as smooth muscle cells (SMC) 76 .…”
Section: Risk Factors That Complicate Hiv-phmentioning
confidence: 99%
“…By binding its receptor VEGFR2, VEGFA regulates angiogenesis and vascular permeability through promoting the proliferation and survival of ECs, where the downstream signaling pathways include phosphoinositide 3 kinase (PI3K)/Akt, focal adhesion kinase (FAK), Rho family GTPases, nitric oxide (NO), and p38 mitogen−activated protein kinase (MAPK) (Claesson-Welsh and Welsh, 2013). Moreover, a recent study showed HIV protein transactivator of transcription (TAT) stimulated the proliferation of pulmonary artery SMCs (PASMCs) through increasing the expression VEGFA, and may be a potential therapeutic target for the treatment of HIV-associated PAH (Guo et al, 2018). SIRT1 is a NAD + -dependent deacetylase shown to play important roles in angiogenesis signaling both in vitro and in mice through controlling the acetylation of the forkhead transcription factor, Foxo1, which is highly expressed in ECs and mediates the expression of angiopoietin 2 (Ang2) (Potente et al, 2005(Potente et al, , 2007.…”
Section: Discussionmentioning
confidence: 99%